O Jeca que virou cultura: recepções críticas à obra cinematográfica de Mazzaropi (1952-2012) - SABADIN, Celso Fabio (2017)
This research had as objective to raise and to study the reception that the films of the actor, director, scriptwriter and Paulista producer Amácio Mazzaropi (1912 - 1981) obtained next to the cinematographic criticism. To this end, a survey was carried out, firstly, with physical and virtual archives of the criticisms published in the most representative print media, preferably in São Paulo and Rio de Janeiro (at the time of Mazzaropi's cinematographic production, the two main cultural and journalistic diffusion of the country), between 1952 and 1980 (period of the production of the films of Mazzaropi). In a second moment, a survey of criticism published between 1981 (year of Mazzaropi's death) and 2012 (year of the celebrations of its centenary of birth) was published. The purpose of the two-period study was to see if, how, and in what proportions it would or would not be possible to verify significant changes in these critical perceptions, and how they became - or not - over the study period, and why. It was also made a specific analysis in all editions of the first phase of the magazine Cultura Cultura (from 1966 to 1988), considered one of the most presentations of the informative news and critic of the Brazilian cinema of this period. In order to contextualize and deepen this study, studies were also carried out on the biographical and artistic trajectory of Amácio Mazzaropi, a survey of the history and development of Brazilian cinematographic criticism, analysis of the forms of classification of the concept of art criticism, as well as research on the construction of the culture and the idol identity, elements, indispensable for the objectives of this study to be fulfilled to the satisfaction. For the field of Communication, this research shows relevance when developing historical counterpoints among the different ways in which film criticism received, perceived, processed and disseminated the work of this filmmaker who is considered the most commercially successful in the history of Brazilian cinema.